Psychological interventions and sports performance: A systematic and bibliometric review - Khandare, Ravindra Baliram (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. This trend supports the importance of developing psychological interventions in sport contexts and suggests that the field has potential for further growth, both in terms of theoretical and applied research. This study aimed to systematically review and analyze the scientific literature on psychological interventions in relation to sports performance through a bibliometric approach. Material and Methods. Using a comprehensive search strategy across Scopus databases. Relevant publications from 2013 to 2024 were identified and examined based on authorship, institutional affiliation, country of origin, publication source, and subject area. The strategy process used PICO and PRISMA with the final result of 20 articles. Results. The findings show that research output on this topic has gradually increased over the years, with significant contributions from the United States, Spain and the United Kingdom. The most prominent subject areas include psychology, health professions and medicine, underlining the multidisciplinary nature of the field. Notably, no single author or institution dominates the field, indicating diverse and globalized research interests. Journals such as Healthcare Switzerland and the Journal of Physical Education and Sport have emerged as key publication platforms. Conclusions. This review highlights the growing recognition of the role of psychological interventions in improving athletic performance, while identifying gaps and future directions for research in this domain.